Lack Of IL-7 And IL-15 Signaling Affects Interferon-gamma Production by, More than Survival of, Small Intestinal Intraepithelial Memory CD8(+) T Cells - Isakov, Dmitry (Eur J Immunol, 2011)
Survival of antigen-specific CD8(+) T cells in peripheral lymphoid organs during viral infection is known to be dependent predominantly on IL-7 and IL-15. However, little is known about a possible influence of tissue environmental factors on this process. To address this question we studied survival of memory antigen-specific CD8(+) T cells in the small intestine. Here, we show that 2 months after vaccinia virus infection, B8R(20–27)/H2-K(b) tetramer(+) CD8(+) T cells in the small intestinal intraepithelial (SI-IEL) layer are found in mice deficient in IL-15 expression. Moreover, SI-IEL and lamina propria lymphocytes do not express the receptor for IL-7 (IL-7Rα/CD127). In addition, after in vitro stimulation with B8R(20–27) peptide, SI-IEL cells do not produce high amounts of IFN-γ either at 5 days (5d) or at 2 months post infection (p.i.). Importantly, the lack of IL-15 was found to shape the functional activity of antigen-specific CD8(+) T cells, by narrowing the CTL avidity repertoire. Taken together, these results reveal that survival factors as well as functional activity of antigen-specific CD8(+) T cells in the SI-IEL compartments may markedly differ from their counterparts in peripheral lymphoid tissues.